Verifying the Determinants of the Mortgage Defaults on Home Mortgage - Wu, Wei-Wen; Li, Jian-Fa; Hong, Cheng-Yih (International Journal of Economics and Financial Issues, 2017)
Banks face severe challenges pertaining to their operations owing to changes in the financial environment. Identifying methods for reducing mortgage defaults and lowering the ratio of nonperforming loans is crucial. Mortgage defaults occur because of complex factors. The present study developed a DEMATEL (Decision Making Trial and Evaluation Laboratory. The results confirmed that the methods proposed by this study feature high applicability and are able to identify the key factors contributing to the mortgage defaults for commercial banks (CBs) and local banks (LBs). In addition, the methods could verify the determinants of the mortgage defaults for both commercial banks and local banks and uncover the differences that exist between the two patterns of mortgage defaults, and provide valuable information for bank management to make better decisions during the development of loan strategies. Keywords: Mortgage default, DEMATEL, Decision Making. JEL Classifications: C02, C18, G32